A Study of Inventory Replenishment Policy for Online Marketing Business A Case Study of Bedding, Furniture, and Home Appliances - Pakdeewanich, Chitsanu; Tumrongsuk, Suchadee (Rajapark Journal, 2021)
This research aims to (1) analyze the inventory shortage problem and (2) study the inventory replenishment policy. The case study is the category of bedding, furniture, and home appliances, and each class has many codes and a variety of demands. It investigated order planning and identifying the suitable quantity of stock to avoid stock quantities falling to a level where orders could not be fulfilled. We then applied a cause and effect diagram to find the root cause of this problem. It showed no minimum inventory level for each category and no categorization of high-selling products. We then categorized each product using ABC Classification, and we computed safe stock levels and economic order quantity for A-class products. The results showed that these methods could reduce stockout in the warehouse for bedding - reducing from 5.90% to 0.42%. House appliances reduced from 3.05% to 0.21%, with no items being out of stock for furniture. Based on the results, entrepreneurs in online business could use these principles to reduce costs in the shortage of delivery.